Respon Bangladesh Terhadap Fenomena Human Trafficking Rohingya di Myanmar - Amalia, Tiara; Lubis, Flori Mardiani; Gustianti, Nurbani Adine (Jurnal Ilmiah Wahana Pendidikan, 2025)
The troubling act of Human Trafficking has cost a million lives Rohingya ethnicity in Myanmar. Everybody have rights in freedom, to live and also being protected. The conflict that the Rohingya ethnicity in Myanmar experienced by the Rohingya has claimed many lives, both children and adults, this act causing buildup at refugee camps in bangladesh. This exploitation act is being a cause of the Transnational Crime, such as slavery, human trafficking and made the object of sexual workers. The Bangladesh government has given a positive response, namely by making efforts to allocate Rohingya refugees to Bhasan Char island, and cooperation between UNHCR and the Bangladesh government through the Repatriation program.